Technical efficiency and returns to scale on banking sector: empirical evidence from GCC countries - Kamarudin, Fakarudin; Sufian, Fazlan; Md Nassir, Annuar (Universiti Putra Malaysia Press, 2015)
This paper investigates the efficiency level of Gulf Cooperation Council (GCC) banks on technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE). Both PTE and SE represent potential factors that influence the efficiency of GCC banks. This study investigates a total of 43 GCC banks over the time period of 2007 to 2011. Data Envelopment Analysis (DEA), a non-parametric method using variable returns to scale (VRTS) under the Banker, Charnes, and Cooper (BCC) model, was applied, with assets and deposit as input, and loan and income as output. On average, results revealed that GCC Banks operate with an optimal scale. Nevertheless, the results were contaminated by the managerial inefficiency in utilising the recourses, although TE, or managerial efficiency, increased to 83.6% in 2011. Furthermore, the results also indicated that, while larger banks (the 22 largest) tend to operate at constant returns to scale (CRS) or decreasing returns to scale (DRS), smaller banks (the 21 smallest) were susceptible to operate at either CRS or increasing returns to scale (IRS).